The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1103/physrevb.88.085405
|View full text |Cite
|
Sign up to set email alerts
|

RKKY interaction between adsorbed magnetic impurities in graphene: Symmetry and strain effects

Abstract: The growing interest in carbon-based spintronics has stimulated a number of recent theoretical studies on the RKKY interaction in graphene, with the aim of determining the most energetically favourable alignments between embedded magnetic moments. The RKKY interaction in undoped graphene decays faster than expected for conventional two-dimensional materials and recent studies suggest that the adsorption configurations favoured by many transition-metal impurities may lead to even shorter ranged decays and possi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…In many of the above studies, it was found that strain is not only useful in stabilizing atoms and molecules adsorbed on the 2D materials, it is also effective in tuning the magnetic properties of these 2D materials . Besides examples already mentioned above, Xu et al found, based on first‐principles calculations, that a moderate biaxial tensile strain (4%) is able to change pristine NbSe 2 and NbS 2 from the AFM ground state to the FM state.…”
Section: Spin Generationmentioning
confidence: 95%
“…In many of the above studies, it was found that strain is not only useful in stabilizing atoms and molecules adsorbed on the 2D materials, it is also effective in tuning the magnetic properties of these 2D materials . Besides examples already mentioned above, Xu et al found, based on first‐principles calculations, that a moderate biaxial tensile strain (4%) is able to change pristine NbSe 2 and NbS 2 from the AFM ground state to the FM state.…”
Section: Spin Generationmentioning
confidence: 95%
“…In undoped graphene a decay rate of D −3 for substitutional, top-adsorbed, and bridge-adsorbed impurities is found, while a much faster decay rate of D −7 is found for center-adsorbed impurities. 13,14,20,23 This decay rate is faster than the D −2 decay expected for conventional two-dimensional materials and arises from the vanishing density of states at the Fermi energy in graphene. 26 This fast decay rate results in the interaction being very short ranged and any method of amplifying the coupling to extend its range could prove useful for both the experimental detection of the RKKY interaction and future spintronic applications.…”
Section: Introductionmentioning
confidence: 86%
“…In the present work, we also aim to extract the direct signatures of these ICM via Ruderman-Kittel-Kasuya-Yosida (RKKY) [30][31][32] exchange interaction between two magnetic impurities placed across the DW created in gapped graphene and in WSM with broken IS. It is an indirect exchange interaction mediated by the conduction electrons of the host material and already investigated extensively in different Dirac materials [33][34][35][36][37][38][39], topological insulators [40], etc. RKKY exchange interaction has also been proposed to determine the magnetic ordering in spin glasses [41] and alloys [42] and to probe topological phase in silicene [43], edge states of graphene nanoribbon [44] and 2D topological insulators [45], decoupled edge modes in phosphorene [46], order of tilting in the spectrum of borophene [47] and the Fermi arc in WSM thin films [48], etc.…”
Section: Introductionmentioning
confidence: 99%